Exploring the Effectiveness and Specific Teaching Methods of English Etymology in Expanding Mental Lexicon for College Students - Guo, Liuniu (Journal of Educational Research and Policies, 2024)
English etymology, as a discipline that studies the origin and development of words, reveals the intrinsic connection and meaning of vocabulary by tracing the historical background, etymology and semantic evolution of words, which not only helps learners to understand the deeper meaning of vocabulary, but also expands and builds their English mental lexicon effectively, thus helping students achieve effective vocabulary enhancement in a short time. The purpose of this paper is to discuss the role of English etymology in the construction and expansion of mental lexicon, analyze its actual teaching methods, and demonstrate its application and effect in educational practice.